Effect of Chloride Ions on the Corrosion Behavior of Al – Zn Alloy in NaOH Solution at Four Different Temperatures - Majed, Rana A.; Al-Kaisy, Hanaa A.; Al-Atrakchy, Hind B. (Al-Khwarizmi Engineering Journal, 2008)
This research involves study effect of chloride ions in concentration range (0.01 – 0.50 mol.dm-3) on the corrosion behavior of Al-Zn alloy in basic media of 1x10-3 mol.dm-3 NaOH at pH=11 and four different temperatures in the range (298-313 K). Cathodic and anodic Tafel slopes (bc &ba) and transfer coefficients (αc & αa) were calculated and the results interprets according to the variation of the rate – determining steps. The results also indicate that the chloride ions are bonded chemically in the interface as an initial step of formation of different mixed oxohydroxy – and chloro complexes. Polarization resistance (Rp) is calculates and interprets the different polarization behavior because of addition of chloride ions to the basic media.